Leaves of Clerodendrum wallichi Merr. Exhibit Analgesic, Antioxidant and Cytotoxic Activities (Bangladesh Pharmaceutical Journal, 2019)
The present study was conducted to evaluate the analgesic, antioxidant and cytotoxic activities of leaves of Clerodendrum wallichii Merr. The analgesic activity of the crude methanolic extract of C. wallichii (MECW) was determined by tail flick- and acetic acid-induced writhing method in Swiss albino mice. In tail flick method, oral administration of MECW at 400 mg/kg body weight exhibited 362.19% elongation of pain response in experimental mice at 60 min. The same dose of plant extract significantly (p < 0.05) inhibited the acetic acid-induced abdominal constrictions in mice and this effect was dose-dependent. In addition, the methanol extract of C. wallichii (MECW) and its petroleum-ether (PESF), chloroform (CSF), dichloromethane (DCMSF) and aqueous (AQSF) soluble fraction were subjected to assay for determination of total phenol content, antioxidant and cytotoxic activities test by standard protocols. The highest amount of phenolic content was present in the MECW (75.44±0.68 mg of GAE/g of extract) while the AQSF displayed the highest free radical scavenging capacity (IC50 value of 7.23±0.05 μg/ml) as compared to 25.18±1.89 μg/ml exhibited by the standard butylated hydroxyl toluene (BHT). In brine shrimp lethality test, the number of surviving shrimp nauplii was counted and LC50 was assessed after 24 h. Both MECW and its PESF exhibited maximum toxicity towards brine shrimp with LC50 value of 10.3±0.01 μg/ml with respect to standard vincristine sulfate (having LC50 of 0.45 μg/ml). The results of the present investigations suggest that methanolic extract of C. wallichii possesses analgesic, antioxidant and cytotoxic activities, confirming the traditional use of the plant.Bangladesh Pharmaceutical Journal 22(2): 208-213, 2019